(untitled) (Malay Literature, 2014)
Arena Wati (1925-2009), is well-known by the Award of Malaysian National Laureate, which he received in 1988 for his outstanding contributions to the development of Malay literature. However he was also the captain of a sailing ship. His familial origins as sailors of Makassar, South Sulawesi, Indonesia have greatly influenced his writings. This article is a scrutiny of a work by Arena Wati in his capacity as a ship captain in relation to two functions, namely "as a trader" and "as a navigator". The approach to the text is through a qualitative content analysis, that is, interpretation and evaluation of messages associated with the text under study, namely, Arena Wati’s memoir entitled Memoir Arena Wati Enda Gulingku (1991). Based on his successful implementation of both the functions mentioned, the analysis reveals that Arena Wati is an accomplished navigator. His knowledge of the maritime trade and the navigation he practiced establishes that Arena Wati’s greatness as a ship captain is equal to his greatness as a fiction writer. Keywords: ship captain, sailor, trader, maritime, navigator